Expression of CXCL5 Gene in Patients Suffering from Non-Small Cell Lung Cancer - Dashtbayazi, Azam; Asghari Moghaddam, Nastaran; Behzadi Andouhjerdi, Roudabeh (Archives of Advances in Biosciences, 2019)
Introduction: Lung cancer is one of the most common cancers with high mortality rate because of the late diagnosis. The present study aimed to quantitatively measure the C-X-C Motif Chemokine Ligand 5 (CXCL5) gene expression level in tissue samples of lung cancer patients to investigate its value as a biomarker during lung cancer diagnosis and screening. Materials and Methods: Tissue samples were collected from 30 patients. Total RNA was extracted from tumor and normal tissues of patients. The rate of CXCL5 gene expression was initially measured in A549 cell line and next, the expression level of this gene in tumor tissue samples of patients suffering from Non-Small Cell Lung Cancer was compared to the normal lung tissue of the same patients. Results: The results demonstrated significant increase of CXCL5 gene expression in cancer samples compared to normal tissues of the same samples. The increase was 5.8 fold for cancerous tissues in comparison with normal tissues (P=0.03). There was no difference between the tumor type (adenocarcinoma, squamous cell carcinoma) and average CXCL5 gene expression rate (P=0.09). In cancerous samples, the expression level of CXCL5 was higher in men compared with those of women (P=0.04). There was no relationship between the change of gene expression and the age of the patients (p=0.08). Conclusion: Based on the results, it can be concluded that the quantitative expression level of CXCL5 in lung cancer patients could be used as a biomarker to screen lung cancer samples, regardless of age of patients and tumor type. However, it can discriminate the stage of tumor.